The Mediating Role of Health Literacy in The Relationship Between Health Information Access, Family Support, and Dietary Adherence Among Rural Hypertensive Patients in Lumajang - Eta Devi Amalia; Ancah Caesarina Novi Marchianti; Tantut Susanto (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2026)
Hypertension remains a major public health problem in Indonesia. Many patients fail to adhere to dietary recommendations despite increasing access to health information, indicating a gap between information exposure and dietary behavior. This study aimed to examine the influence of health information access and family support on health literacy and dietary adherence among hypertensive patients in Lumajang Regency. A cross-sectional study was conducted among 227 hypertensive patients aged 17–65 years recruited from four primary healthcare centers using probability sampling. Health information access was measured using the Health Information National Trends Survey, health literacy using the Health Literacy Survey – European Union Questioners version Indonesia (HLS-EU-Q12 ID), dietary adherence using the Dietary Approaches to Stop Hypertension Questionnaire, and family support was also assessed. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that greater access to health information was associated with higher health literacy (β=0.150, p=0.035), but with a lower likelihood of dietary adherence (β = −0.251, p < 0.001). Family support increased the likelihood of higher health literacy (β = 0.241, p < 0.001) and better dietary adherence (β = 0.135, p = 0.038), while higher health literacy substantially increased the likelihood of dietary adherence (β = 0.277, p < 0.001). These findings indicate that increased exposure to health information does not automatically lead to healthier dietary behavior. Family support plays a crucial role in translating health knowledge into practice, highlighting the importance of family involvement and practical, easy-to-understand health information to improve dietary adherence among rural hypertensive patients in rural areas.